2002
DOI: 10.1351/pac200274081469
|View full text |Cite
|
Sign up to set email alerts
|

Role of gene regulation in the anticancer activity of carotenoids

Abstract: There is extensive evidence that high intake of fruits and vegetables is associated with decreased risk of many types of cancers. Thus, it is widely accepted that diet changes are a powerful means to prevent cancer. Although there is a growing interest in the role of the tomato carotenoid lycopene in cancer prevention and treatment, we hypothesize that a single micronutrient cannot replace the power of the concerted action of multiple agents derived from a diet rich in fruits and vegetables. Indeed, we found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…hormones, antibodies, lipids), or carotenoid-driven mechanisms other than antioxidant action (e.g. regulation of immune-response genes; Sharoni et al 2002), affect immune-system organization or beak-color development.…”
Section: Discussionmentioning
confidence: 99%
“…hormones, antibodies, lipids), or carotenoid-driven mechanisms other than antioxidant action (e.g. regulation of immune-response genes; Sharoni et al 2002), affect immune-system organization or beak-color development.…”
Section: Discussionmentioning
confidence: 99%
“…Antiproliferative effects of lycopene have been reported in several cancer cell lines including those derived from prostate cancers and prostate epithelial cells [55, 80, 97, 107-122]. For example, a lower dose of lycopene inhibited the growth of LNCaP prostate cancer cells while a higher dose blocked cells in G2/M phase and induced apoptosis [112].…”
Section: Lycopene Tomatoes and Prostate Cancers: Mechanismsmentioning
confidence: 99%
“…Recent epidemiological studies suggested that higher dietary intake of lycopene is correlated with a lower circulating IGF-I and higher levels of IGFBPs [122, 130, 131]. Lycopene at pharmacologic concentrations inhibited prostate cancer cell IGF-I receptor expression and Akt phosphorylation [114].…”
Section: Lycopene Tomatoes and Prostate Cancers: Mechanismsmentioning
confidence: 99%
“…In addition, our results provide a basic knowledge about phytochemicals interactions with biological systems that may be useful for the design of functional foods. Sharoni et al [53] hypothesized that a single micronutrient cannot replace the power of the concerted action of multiple agents derived from a diet rich in fruits and vegetables.…”
Section: Discussionmentioning
confidence: 99%